Analysis of Environmental Graphic Design: A Study Case from Hospital in Indonesia - Aziz, Malik Abdul; Iskandar, M Syahril (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Environmental Graphic Design (EGD) is one of the roles of graphic design objects in an area. The goal is to provide information about the placement and identity of a place. EGD should had the standardization which had in several areas as corporate identity, one of them is a hospital. Pondok Indah Group Hospital (RSPI) is a private hospital that manages three hospitals in Indonesia, one of is RSPI-Bintaro. The main problem is the differences in EGD from each branch. This makes the difference in an EGD identity from each RSPI, one of them is the EGD at RSPI-Bintaro. The research was conducted at RSPI – Bintaro in an outdoor area (Signage exterior). This study uses a descriptive method to be able to describe and classify EGD at RSPI-Bintaro. This research goal is conducted to describe the EGD, especially the signage for the RSPI-Bintaro area in terms of visual elements and functions. The benefits of this research add to the scientific body of EGD in Hospitals. Besides, the exterior signage of the RSPI-Bintaro area is quite good and informative have comparedto other branch hospitals.